Genetic and Functional Associations with Decreased Anti-inflammatory Tumor Necrosis Factor Alpha Induced Protein 3 in Macrophages from Subjects with Axial Spondyloarthritis - Liu, Yiping; Ye, Zhan; Li, Xiang; Anderson, Jennifer L.; Khan, Mike; DaSilva, Douglas; Baron, Marissa; Wilson, Deborah; Bocoun, Vera; Ivacic, Lynn C.; Schrodi, Steven J.; Smith, Judith A. (Frontiers in Immunology, 2017)
Objective: TNFAIP3 is an anti-inflammatory protein implicated in multiple autoimmune and rheumatologic conditions. We hypothesized that lower levels of TNFAIP3 contributes to excessive cytokine production in response to inflammatory stimuli in axial spondyloarthritis. A further aim was to determine the immune signaling and genetic variation regulating TNFAIP3 expression in individual subjects. Methods: Blood derived macrophages from 50 axial spondyloarthritis subjects and 30 healthy controls were assessed for TNFAIP3 expression. Cell lysates were also analyzed for NF-kappaB, MAP kinase and STAT3 phosphorylation and supernatants for cytokine production. Coding and regulatory regions in the TNFAIP3 gene and other auto-inflammation implicated genes were sequenced by Next Generation sequencing and variants identified. Results: Mean TNFAIP3 was significantly lower in spondyloarthritis macrophages than controls (p=0.0085). Spondyloarthritis subject macrophages correspondingly produced more TNF-alpha in response to lipopolysaccharide (LPS, p=0.015). Subjects with the highest TNFAIP3 produced significantly less TNF-alpha in response to LPS (p=0.0023). Within axial spondyloarthritis subjects, those on TNF blockers or with shorter duration of disease expressed lower levels of TNFAIP3 (p=0.0011 and 0.0030 respectively). TNFAIP3 expression correlated positively with phosphorylated IkappaBalpha, phosphorylated MAP kinases, and unstimulated phosphorylated STAT3, but negatively with LPS or TNF-alpha-stimulated fold induction of phosphorylated STAT3. Further, subjects with specific groups of variants within TNFAIP3 displayed differences in TNFAIP3 (p=0.03-0.004). Nominal pQTL associations with genetic variants outside TNFAIP3 were identified. Conclusions: Our results suggest both immune functional and genetic variation contribute to the regulation of TNFAIP3 levels in individual subjects. Decreased expression of TNFAIP3 in axial spondyloarthritis macrophages correlated with increased LPS-induced TNF-alpha, and thus TNFAIP3 dysregulation may be a contributor to excessive inflammatory responses in spondyloarthritis subjects.